Composition for selectively degrading aniline pollutants, preparation method and application thereof
By using composite materials combined with cellulose carrier and phenolic compounds in wastewater treatment, and a composition with periodate or permanganate as oxidizing agents, the problem that the removal effect of aniline pollutants in wastewater is affected by the water quality matrix is solved, efficient and selective pollutant removal is achieved, and the toxicity of wastewater is reduced.
Patent Information
- Application Number
- CN202310189919.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-02-28
AI Technical Summary
The prior art is susceptible to the influence of water matrix when removing aniline pollutants in wastewater, resulting in poor removal effect.
A composition for selectively degrading aniline contaminants is provided, including a composite material and an oxidant, which is provided with cellulose as a carrier, and is supported by two ortho-phenolic hydroxyl groups, and the oxidant includes periodate and/or permanganate. The composition can efficiently remove aniline contaminants in wastewater.
This composition can selectively oxidize phenolic compounds to form quinone active species. The quinone active species react with aniline contaminants to achieve efficient removal and do not react with the water matrix, avoiding the inhibition of the removal effect. At the same time, quinone by-products are loaded in the composite material, which is easy to recover and reduces the toxicity of wastewater.
Smart Images

Figure CN116216905B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and particularly relates to a composition for selectively degrading aniline pollutants, a preparation method and application thereof. Background Art
[0002] As an important chemical raw material, aniline is widely used in dye, medicine and rubber industries. With the development of industrial level and the increase of human demand for chemical products, the demand for aniline has increased, resulting in an increase in the concentration of aniline pollutants in the environment. At present, aniline pollutants of different concentration levels (ng / L-μg / L) have been detected in the water environment. Aniline pollutants have the characteristics of wide pollution, many types, long half-life and high toxicity. Long-term exposure to the environment will cause carcinogenicity, teratogenicity and mutagenicity, and have bioaccumulation, causing irreversible damage to human health.
[0003] Although the advanced oxidation process based on hydroxyl radicals that has emerged in recent years can effectively remove aniline pollutants, the water quality matrix in the wastewater will affect the removal effect of aniline pollutants. For example, chloride ions, carbonate ions and dissolved organic matter can react with hydroxyl radicals, consume the concentration of free radicals, and thus inhibit the degradation of aniline pollutants. Therefore, how to avoid the influence of the water quality matrix in wastewater and improve the removal effect of aniline pollutants in wastewater is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a composition for selectively degrading aniline pollutants, which has the advantage of strong resistance to water matrix and can selectively and efficiently remove aniline pollutants in wastewater.
[0005] The first aspect of the present invention provides a composition for selectively degrading aniline pollutants, comprising a composite material and an oxidant, wherein the composite material comprises cellulose as a carrier and a phenolic compound containing two ortho-phenolic hydroxyl groups loaded in the carrier, and the oxidant comprises periodate and / or permanganate.
[0006] Preferably, the periodate includes at least one of sodium periodate, potassium periodate and lithium periodate.
[0007] Preferably, the permanganate includes at least one of potassium permanganate, sodium permanganate and ammonium permanganate.
[0008] Preferably, the phenolic compound containing two ortho-phenolic hydroxyl groups includes at least one of catechol, 4-methylcatechol and 4-ethylcatechol.
[0009] The second aspect of the present invention provides a method for preparing the composition for selectively degrading aniline pollutants according to the present invention, comprising the following steps:
[0010] dissolving the phenolic compound containing two ortho-phenolic hydroxyl groups and the cellulose in an ionic liquid to obtain a mixed solution;
[0011] adding the mixed solution dropwise into water, so that the mixed solution forms a pre-composite material;
[0012] washing the pre-composite material with water, and drying to obtain a composite material;
[0013] The composite material and the oxidant are mixed to obtain the composition for selectively degrading aniline pollutants.
[0014] Preferably, the method for preparing the composition for selectively degrading aniline pollutants of the present invention comprises the following steps:
[0015] The specific process of the dissolution includes: adding the phenolic compound containing two ortho-phenolic hydroxyl groups and the cellulose into the ionic liquid, and stirring for 1-5 hours at a temperature of 65-95° C.
[0016] Preferably, the mass ratio of the phenolic compound containing two ortho-phenolic hydroxyl groups to the cellulose is 1:(0.3-3).
[0017] Preferably, the concentration of the phenolic compound containing two ortho-phenolic hydroxyl groups in the ionic liquid is 16-140 g / L.
[0018] Preferably, the water flushing is performed 3-5 times.
[0019] Preferably, the drying temperature is 20-30°C.
[0020] Preferably, the ionic liquid is 1-allyl-3-methylimidazolium chloride or 1-ethyl-3-methylimidazolium acetate.
[0021] Preferably, the water is ultrapure water.
[0022] The third aspect of the present invention provides the use of the composition for selectively degrading aniline pollutants of the present invention in the preparation of an organic wastewater degradation agent.
[0023] The fourth aspect of the present invention provides a method for selectively degrading aniline pollutants in wastewater, wherein the composition for selectively degrading aniline pollutants of the present invention is added into the wastewater, the input amount of the composite material is 10-15 g / L, and the input amount of the oxidant is 20-40 μM.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0025] In the composition for selectively degrading aniline pollutants of the present invention, an oxidant can selectively oxidize a phenolic compound containing two ortho-phenolic hydroxyl groups in the composite material in wastewater to generate quinone active species. The quinone active species is an active species that can selectively react with aniline pollutants with strong nucleophilic ability and does not react with a water matrix, thereby being able to selectively and efficiently remove aniline pollutants in wastewater. Since toxic quinone by-products are generated by addition reactions between quinone active species and aniline pollutants, the present invention adopts a composite material so that the generated quinone by-products are loaded in the composite material, which is easy to recover and reduces the toxicity of the wastewater. The composite material has good stability, strong repeatability and can be recycled. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0027] Figure 1 is a physical picture of the composite material of Example 1;
[0028] Figure 2 is a graph showing the degradation of aniline by the composition of Example 1 and sodium periodate alone or the composite material;
[0029] Figure 3 is a cycle effect diagram of the composition of Example 1 on aniline degradation;
[0030] Figure 4 is a graph showing the degradation of aniline in different water bodies by the composition of Example 1;
[0031] Figure 5 The graph is a degradation curve of aniline by the composition of Example 2 and potassium permanganate alone. DETAILED DESCRIPTION
[0032] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0033] Unless otherwise specified, the raw materials, reagents and devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0034] Example 1
[0035] A composition for selectively degrading aniline pollutants comprises a composite material and sodium periodate. The composite material comprises cellulose as a carrier and catechol loaded in the carrier.
[0036] The preparation method of the composition for selectively degrading aniline pollutants comprises the following steps:
[0037] (1) 0.5 g of α-cellulose and 0.5 g of catechol were placed in a 50 mL brown bottle, and 10 mL of 1-allyl-3-methylimidazolium chloride ionic liquid was added. The mixture was stirred with a rotor, and then the mixed solution was placed in a water bath, heated to 85° C., and stirred at the constant temperature for 3 hours.
[0038] (2) adding the heated mixed solution into a plastic syringe with a 26-G needle, and using external force to drop the mixed solution evenly and slowly into a 50 mL beaker containing ultrapure water to prepare a pre-composite material, and then washing the pre-composite material with ultrapure water for 3 times, and drying it at 25° C. for 24 hours to obtain a composite material (denoted as catechol@cellulose microspheres);
[0039] (3) The composite material is mixed with sodium periodate to prepare a composition for selectively degrading aniline pollutants (denoted as sodium periodate / catechol@cellulose microspheres).
[0040] like Figure 1 As shown, the composite material prepared in this embodiment has a regular morphology, uniform particle size, and is transparent.
[0041] Test on Degradation of Aniline Pollutants
[0042] 1. Sodium periodate / catechol@cellulose microspheres degrade aniline in water.
[0043] Under the conditions of pH=7±0.2, solid-liquid ratio of catechol@cellulose microspheres to aniline aqueous solution of 10 g / L, sodium periodate dosage of 20 μM, reaction temperature of 20°C, and degradation time of 60 s, the degradation effects of sodium periodate / catechol@cellulose microspheres provided in Example 1, sodium periodate alone, and catechol@cellulose microspheres alone on aniline in 50 mL of 5 μM aniline aqueous solution were investigated. Figure 2 As shown. Figure 2 It can be seen that when sodium periodate was added alone, aniline was degraded to 0 within 60 seconds; when catechol@cellulose microspheres were added alone, aniline was degraded to 0 within 60 seconds; when sodium periodate / catechol@cellulose microspheres were added, aniline was completely degraded after 60 seconds of reaction. This shows that sodium periodate combined with catechol@cellulose microspheres can effectively degrade aniline in water.
[0044] 2. Cycle experiment of sodium periodate / catechol@cellulose microspheres to degrade aniline in water.
[0045] Under the conditions of pH=7±0.2, solid-liquid ratio of catechol@cellulose microspheres to aniline aqueous solution of 10g / L, sodium periodate dosage of 20μM, reaction temperature of 20℃, and degradation time of 60s, the recyclability of catechol@cellulose microspheres after degradation of aniline by sodium periodate / catechol@cellulose microspheres provided in Example 1 in 150mL of 5μM aniline aqueous solution was investigated. After each degradation, the catechol@cellulose microspheres were fished out and rinsed with ultrapure water 3 times, and dried at room temperature for 24 hours before the next use. Figure 3 As shown. Figure 3 It can be seen that the addition experiment of sodium periodate and catechol@cellulose microspheres was repeated 5 times, and aniline was completely degraded after each cycle reaction for 60 seconds. This experiment shows that catechol@cellulose microspheres have good reusability.
[0046] 3. Sodium periodate / catechol@cellulose microspheres degrade aniline in actual water bodies.
[0047] Under the conditions of a solid-liquid ratio of catechol@cellulose microspheres to aniline aqueous solution of 10 g / L, a sodium periodate dosage of 40 μM, a reaction temperature of 20°C, and a degradation time of 60 s, the degradation effect of sodium periodate / catechol@cellulose microspheres provided in Example 1 on aniline in 50 mL of 5 μM aniline aqueous solutions (river water, sewage, and landfill leachate) was investigated. These water bodies contain chloride ions, carbonate ions, sulfate ions, bromide ions, nitrate ions, and dissolved organic matter, etc. Ultrapure water was used as a control. Figure 4 As shown. Figure 4 It can be seen that when sodium periodate and catechol@cellulose microspheres were added to river water, sewage and landfill leachate containing aniline and reacted for 60 seconds, aniline could be completely degraded. This shows that sodium periodate combined with catechol@cellulose microspheres can efficiently degrade aniline in different actual water bodies and is basically not affected by the water quality matrix.
[0048] Example 2
[0049] A composition for selectively degrading aniline pollutants comprises a composite material and potassium permanganate. The composite material comprises cellulose as a carrier and catechol loaded in the carrier.
[0050] The preparation method of the composition for selectively degrading aniline pollutants comprises the following steps:
[0051] (1) 0.25 g of α-cellulose and 0.7 g of catechol were placed in a 50 mL brown bottle, and 5 mL of 1-ethyl-3-methylimidazolium acetate ionic liquid was added. The mixture was stirred with a rotor, and then the mixed solution was placed in a water bath, heated to 65° C., and stirred at the constant temperature for 5 hours.
[0052] (2) adding the heated mixed solution into a plastic syringe with a 26-G needle, and using external force to drop the mixed solution evenly and slowly into a 50 mL beaker containing ultrapure water to prepare a pre-composite material, and then washing the pre-composite material with ultrapure water for 3 times, and drying it at 20° C. for 24 hours to obtain a composite material (denoted as catechol@cellulose microspheres);
[0053] (3) The composite material and potassium permanganate are mixed to prepare a composition for selectively degrading aniline pollutants (denoted as potassium permanganate / catechol@cellulose microspheres).
[0054] Experiment on the degradation of aniline in water by potassium permanganate / catechol@cellulose microspheres.
[0055] Under the conditions of pH=7±0.2, solid-liquid ratio of catechol@cellulose microspheres to aniline aqueous solution of 10 g / L, potassium permanganate dosage of 20 μM, reaction temperature of 20°C, and degradation time of 60 s, the degradation effects of potassium permanganate / catechol@cellulose microspheres provided in Example 2 and potassium permanganate alone on aniline in 50 mL of 5 μM aniline aqueous solution were investigated. Figure 5 As shown. Figure 5 It can be seen that when potassium permanganate is added alone, aniline is degraded to 0 within 60 seconds; when potassium permanganate / catechol@cellulose microspheres are added, aniline is completely degraded after 60 seconds of reaction. This shows that potassium permanganate combined with catechol@cellulose microspheres can efficiently degrade aniline in water.
[0056] Example 3
[0057] A composition for selectively degrading aniline pollutants comprises a composite material and potassium periodate. The composite material comprises cellulose as a carrier and catechol loaded in the carrier.
[0058] The preparation method of the composition for selectively degrading aniline pollutants comprises the following steps:
[0059] (1) 0.7 g of α-cellulose and 0.25 g of catechol were placed in a 50 mL brown bottle, and 15 mL of 1-ethyl-3-methylimidazolium acetate ionic liquid was added. The mixture was stirred with a rotor, and then the mixed solution was placed in a water bath and heated to 95° C., and stirred at the constant temperature for 1 hour.
[0060] (2) adding the heated mixed solution into a plastic syringe with a 26-G needle, and using external force to drop the mixed solution evenly and slowly into a 50 mL beaker containing ultrapure water to prepare a pre-composite material, and then washing the pre-composite material with ultrapure water for 5 times, and drying it at 30° C. for 24 hours to obtain a composite material (denoted as catechol@cellulose microspheres);
[0061] (3) The composite material is mixed with potassium periodate to prepare a composition for selectively degrading aniline pollutants (denoted as potassium periodate / catechol@cellulose microspheres).
[0062] Example 4
[0063] The difference from Example 1 is that in Example 4, sodium periodate is replaced by lithium periodate, and the other components and preparation methods are the same as those of Example 1. The composition for selectively degrading aniline pollutants provided in Example 4 is recorded as lithium periodate / catechol@cellulose microspheres.
[0064] Example 5
[0065] The difference from Example 1 is that in Example 5, sodium periodate is replaced by sodium permanganate, and the other components and preparation methods are the same as those of Example 1. The composition for selectively degrading aniline pollutants provided in Example 5 is recorded as sodium permanganate / catechol@cellulose microspheres.
[0066] Example 6
[0067] The difference from Example 1 is that in Example 6, sodium periodate is replaced by ammonium permanganate, and the other components and preparation methods are the same as those of Example 1. The composition for selectively degrading aniline pollutants provided in Example 6 is denoted as ammonium permanganate / catechol@cellulose microspheres.
[0068] Example 7
[0069] The difference from Example 1 is that in Example 7, catechol is replaced by 4-methylcatechol, and the other components and preparation methods are the same as those of Example 1. The composition for selectively degrading aniline pollutants provided in Example 7 is recorded as sodium periodate / 4-methylcatechol@cellulose microspheres.
[0070] Example 8
[0071] The difference from Example 1 is that in Example 8, catechol is replaced by 4-ethylcatechol, and the other components and preparation methods are the same as those of Example 1. The composition for selectively degrading aniline pollutants provided in Example 8 is recorded as sodium periodate / 4-ethylcatechol@cellulose microspheres.
[0072] Test on Degradation of Aniline Pollutants
[0073] 1. Under the conditions of pH = 7±0.2, the solid-liquid ratio of the composite material to the aniline aqueous solution was 10 g / L, the dosage of the oxidant was 20 μM, the reaction temperature was 20°C, and the degradation time was 60 s, the degradation effect of the composition for selectively degrading aniline pollutants provided in Examples 3-8 on aniline in 50 mL of 5 μM aniline aqueous solution was investigated.
[0074] Test results: When the compositions for selectively degrading aniline pollutants provided in Examples 3-8 were added respectively, aniline could be completely degraded after 60 seconds of reaction, indicating that the compositions for selectively degrading aniline pollutants provided by the present invention can efficiently degrade aniline in water.
[0075] 2. Under the conditions of pH=7±0.2, solid-liquid ratio of composite material to aniline aqueous solution of 10 g / L, dosage of oxidant of 20 μM, reaction temperature of 20°C, and degradation time of 60 s, the composite materials provided in Examples 3-8 were respectively investigated for their recyclability after degradation of aniline in 150 mL of 5 μM aniline aqueous solution. After each degradation, the composite material was fished out and rinsed with ultrapure water 3 times, and dried at room temperature for 24 hours before next use.
[0076] Test results: The addition experiment of the composite material provided in Examples 3-8 was repeated 5 times, and after each cycle reaction for 60 seconds, aniline could be completely degraded, indicating that the composite material provided by the present invention has good reusability.
[0077] 3. Under the conditions that the solid-liquid ratio of the composite material to the aniline aqueous solution is 15 g / L, the dosage of the oxidant is 40 μM, the reaction temperature is 20°C, and the degradation time is 60 s, the degradation effect of the composition for selectively degrading aniline pollutants provided in Examples 3-8 on aniline in 50 mL of different actual aqueous solutions of 5 μM aniline (river water, sewage and landfill leachate) was investigated respectively.
[0078] Test results: The compositions for selectively degrading aniline pollutants provided in Examples 3-8 were added to river water, sewage and landfill leachate containing aniline, respectively, and reacted for 60 seconds, and aniline was completely degraded. This indicates that the compositions for selectively degrading aniline pollutants provided by the present invention can efficiently degrade aniline in different actual water bodies, and are basically not affected by the water quality matrix.
[0079] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for selectively degrading aniline pollutants in wastewater, characterized in that: Putting a composition for selectively degrading aniline pollutants into wastewater, the composition for selectively degrading aniline pollutants comprising a composite material and an oxidant, the composite material being put in an amount of 10-15 g / L, the oxidant being put in an amount of 20-40 μM, the composite material comprising cellulose as a carrier and a phenolic compound containing two ortho-phenolic hydroxyl groups loaded in the carrier, and the oxidant comprising periodate and / or permanganate; The phenolic compound containing two ortho-phenolic hydroxyl groups is catechol, 4-methylcatechol or 4-ethylcatechol; The composite material is catechol@cellulose microspheres, 4-methylcatechol@cellulose microspheres or 4-ethylcatechol@cellulose microspheres.
2. The method for selectively degrading aniline pollutants in wastewater according to claim 1, characterized in that: The periodate includes at least one of sodium periodate, potassium periodate and lithium periodate.
3. The method for selectively degrading aniline pollutants in wastewater according to claim 1, characterized in that: The permanganate includes at least one of potassium permanganate, sodium permanganate and ammonium permanganate.
4. The method for selectively degrading aniline pollutants in wastewater according to claim 1, characterized in that: The composition for selectively degrading aniline pollutants is prepared by a preparation method comprising the following steps: dissolving the phenolic compound containing two ortho-phenolic hydroxyl groups and the cellulose in an ionic liquid to obtain a mixed solution; adding the mixed solution dropwise into water, so that the mixed solution forms a pre-composite material; washing the pre-composite material with water, and drying to obtain a composite material; The composite material and the oxidant are mixed to obtain the composition for selectively degrading aniline pollutants.
5. The method for selectively degrading aniline pollutants in wastewater according to claim 4, characterized in that: The specific process of the dissolution includes: adding the phenolic compound containing two ortho-phenolic hydroxyl groups and the cellulose into the ionic liquid, and stirring for 1-5 hours at a temperature of 65-95° C.
6. The method for selectively degrading aniline pollutants in wastewater according to claim 4, characterized in that: The mass ratio of the phenolic compound containing two ortho-phenolic hydroxyl groups to the cellulose is 1:(0.3-3).
7. The method for selectively degrading aniline pollutants in wastewater according to claim 4, characterized in that: The concentration of the phenolic compound containing two ortho-phenolic hydroxyl groups in the ionic liquid is 16-140 g / L.
Citation Information
Patent Citations
Method for activation of potassium permanganate in degradation of organic pollutants in water with natural redox mediator
CN110255693A
Cellulose filter membrane for in-situ rapid degradation of organic pollutants in sewage and preparation method thereof
CN110917901A